44th International Conference on Coordination Chemistry (ICCC) Special Collection. Issue 7 (24th January 2023) - Gallo, Emma; Proust, Anna; Pettinari, Claudio
Abstract: Since its beginning in 1893, coordination chemistry has been evolving constantly, and it has become a fundamental pillar for chemical sciences, from catalysis to materials. After two years of restrictions due to the pandemic, the 44 th International Conference on Coordination Chemistry (ICCC) took place in Rimini (Italy) in August 2022. It was the occasion for over thousand chemists to share their research projects, some of which are showcased in this Special Collection. Guest Editors Emma Gallo (University of Milan), Anna Proust (Sorbonne University Paris), and Claudio Pettinari (University of Camerino) summarize the excellent results in the "44 th ICCC" Special Collection. Abstract : The Special Collection "44 th ICCC" showcases research articles and reviews discussed at the 44 th gathering of the prestigious International Conference on Coordination Chemistry (ICCC). Guest Editors briefly introduce the excellent research in this collection.